A comparative analysis of english learning needs among regular students and employee class majors in diploma three of mechanical engineering study program focusing on plantation sector at Polytechnic LPP of Yogyakarta - Endang Lestari (Sean Institute, 2024)
In the contemporary landscape of higher education, the proficiency in English language skills is increasingly recognized as a pivotal asset for academic success and professional advancement. This study embarks on a comparative exploration to discern the nuanced disparities in English learning needs between two distinct cohorts within the Applied Bachelor of Mechanical Technology Study Program at Polytechnic LPP of Yogyakarta: regular students and employees pursuing education through the employee class. Employing a mixed-methods approach, the research endeavors to unravel the multifaceted dimensions of English language acquisition, encompassing both the scholastic exigencies of traditional students and the practical demands encountered by employed learners. There were 41 respondents consisting of 37 from the regular class and 4 from the employee class. The researcher used questionnaires to collect the data. The quantitative data were analyzed using descriptive statistics. The data with highest percentage are presented in the table. Based on the need analysis, the student found descriptive, narrative, recount, procedure and article text in their life. The topics consist of measurement tools, instrumentation, sugar fabrication, tools maintenance, and load tools. Pronunciation and Vocabulary become obstacles in learning English. In speaking activities, they want to have more practice and focus on grammar and pronunciation. The main goal in learning English is to improve their communication skill and career preparation. The role of the lecturer should be interactive with students, become a motivator, and apply new technology and fun learning methods. They prefer to work in group and individual. Online media, book, article, song and movie are their favorite learning source. In general, there are some similarities between regular and employee students' perceptions. The result of this study not only contributes to the academic discourse on language education but also holds pragmatic implications for educational policymakers, administrators, and practitioners vested in optimizing the efficacy and inclusivity of English language instruction within vocational tertiary education settings